2013
DOI: 10.1186/1471-2458-13-1124
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of diabetes mellitus among diabetic patients in the Gambia: a strong case for health education and promotion

Abstract: BackgroundAwareness of various aspects of Diabetes Mellitus (DM) is essential for the prevention, management and control of the disease. However, several studies have consistently shown that awareness of DM in the general population is low. None of these studies, however, was conducted in The Gambia, even though the condition constitutes a major public health problem in the country. In this paper, we assessed the awareness of DM among diabetic patients attending the Medical Out-Patient Department (MOPD) of Roy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
53
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 16 publications
11
53
3
Order By: Relevance
“…5 In a study done in Gambia, it was found that 80% diabetics had a diabetic family member but only one third knew that diabetes could be a hereditary disease. 6 In the present study, about two thirds of the study participants had correct knowledge about symptoms of diabetes. Foma et al reported, about three quarters of the studied patients had correct knowledge about the symptoms of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In a study done in Gambia, it was found that 80% diabetics had a diabetic family member but only one third knew that diabetes could be a hereditary disease. 6 In the present study, about two thirds of the study participants had correct knowledge about symptoms of diabetes. Foma et al reported, about three quarters of the studied patients had correct knowledge about the symptoms of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Foma et al reported, about three quarters of the studied patients had correct knowledge about the symptoms of diabetes. 6 The normal level of glucose in the blood was known to about 50.9% of our participants. This was similar to a study done in Omani patients where 57.5% knew the normal blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…1 India has a high prevalence of diabetes mellitus and the numbers are increasing every year, estimated to be 79.4 million by the year 2030. 2 Uncontrolled diabetes can lead to lifelong complications associated with increased morbidity and mortality like diabetic retinopathy, neuropathy, and cardiovascular disease, it also causes heavy financial burden to the society.…”
Section: Introductionmentioning
confidence: 99%
“…2 Uncontrolled diabetes can lead to lifelong complications associated with increased morbidity and mortality like diabetic retinopathy, neuropathy, and cardiovascular disease, it also causes heavy financial burden to the society. 1 Many patients are aware that they have diabetes only when they develop one of its complications. Knowledge of DM can reduce the incidence of complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation